ON THE STRUCTURE OF MODERN EDUCATIONAL DICTIONARIES (Scientific journal of the Fergana State University, 2023)
The article deals with the composition of the new generation educational dictionaries, the structure and arrangement of its main and auxiliary parts, the definition of language units in the dictionary, the content of dictionary entries, the design and capabilities of the author, as well as the mega, macro and microstructures of modern educational dictionaries